Comparison of thermodynamic database models and APT data for strength modeling in high Nb content γ–γ′ Ni-base superalloys. (5th December 2015) - Antonov, Stoichko; Detrois, Martin; Isheim, Dieter; Seidman, David; Helmink, Randolph C.; Goetz, Robert L.; Sun, Eugene; Tin, Sammy
Abstract: In response to the increasing need for higher operating temperatures in advanced gas turbine engines, new alloying concepts are required to develop novel nickel-base superalloys with enhanced temperature capabilities. Recent studies have shown that polycrystalline Ni-base superalloys containing elevated levels of Nb additions exhibit superior properties at elevated temperatures when compared to existing commercial Ni-base superalloys. In order to design, develop and fully exploit this innovative class of superalloys, an understanding of how alloying elements partition to each phase is essential. Using atom probe tomography (APT), compositions of the constituent phases were measured in four high Nb content γ–γ′ Ni-base superalloys and the results were compared to thermodynamic database models from Thermo-Calc. Results were also used in predicting the solid solution strength behavior of the four alloys. The differences in phase composition predictions from thermodynamic models resulted in dissimilarities between the generated strength behavior curves and those from the experimental work. Graphical abstract: Highlights: Nb alloying additions provide strengthening to both γ and γ′ phases in superalloys. Phase composition data and strength models were used to estimate intrinsic strength. Thermo-Calc predictions of partitioning behavior were compared to APT results.